Extracellular Matrix-derived Peptide Binds to αvβ3 Integrin and Inhibits Angiogenesis - Yohei Maeshima; Udaya Yerramalla; Mohanraj Dhanabal; Kathryn A. Holthaus; Sergei F. Barbashov; Surender Kharbanda; Corinne Reimer; Mark Manfredi; W. Matthew Dickerson; Raghu Kalluri (2001)
Angiogenesis is associated with several pathological disorders as well as with normal physiological maintenance. Components of vascular basement membrane are speculated to regulate angiogenesis in both positive and negative manner. Recently, we reported that tumstatin (the NC1 domain of α3 chain of type IV collagen) and its deletion mutant tum-5 possess anti-angiogenic activity. In the present study, we confirm that the anti-angiogenic activity of tumstatin and tum-5 is independent of disulfide bond requirement. This property of tum-5 allowed us to use overlapping synthetic peptide strategy to identify peptide sequence(s) which possess anti-angiogenic activity. Among these peptides, only the T3 peptide (69–88 amino acids) and T7 peptide (74–98 amino acids) inhibited proliferation and induced apoptosis specifically in endothelial cells. The peptides, similar to tumstatin and the tum-5 domain, bind and function via αvβ3 in an RGD-independent manner. Restoration of a disulfide bond between two cysteines within the peptide did not alter the anti-angiogenic activity. Additionally, these studies show that tumstatin peptides can inhibit proliferation of endothelial cells in the presence of vitronectin, fibronectin, and collagen I. Anti-angiogenic effect of the peptides was further confirmed in vivo using a Matrigel plug assay in C57BL/6 mice. Collectively, these experiments suggest that the anti-angiogenic activity of tumstatin is localized to a 25-amino acid region of tumstatin and it is independent of disulfide bond linkage. Structural features and potency of the tumstatin peptide make it highly feasible as a potential anti-cancer drug. Angiogenesis is associated with several pathological disorders as well as with normal physiological maintenance. Components of vascular basement membrane are speculated to regulate angiogenesis in both positive and negative manner. Recently, we reported that tumstatin (the NC1 domain of α3 chain of type IV collagen) and its deletion mutant tum-5 possess anti-angiogenic activity. In the present study, we confirm that the anti-angiogenic activity of tumstatin and tum-5 is independent of disulfide bond requirement. This property of tum-5 allowed us to use overlapping synthetic peptide strategy to identify peptide sequence(s) which possess anti-angiogenic activity. Among these peptides, only the T3 peptide (69–88 amino acids) and T7 peptide (74–98 amino acids) inhibited proliferation and induced apoptosis specifically in endothelial cells. The peptides, similar to tumstatin and the tum-5 domain, bind and function via αvβ3 in an RGD-independent manner. Restoration of a disulfide bond between two cysteines within the peptide did not alter the anti-angiogenic activity. Additionally, these studies show that tumstatin peptides can inhibit proliferation of endothelial cells in the presence of vitronectin, fibronectin, and collagen I. Anti-angiogenic effect of the peptides was further confirmed in vivo using a Matrigel plug assay in C57BL/6 mice. Collectively, these experiments suggest that the anti-angiogenic activity of tumstatin is localized to a 25-amino acid region of tumstatin and it is independent of disulfide bond linkage. Structural features and potency of the tumstatin peptide make it highly feasible as a potential anti-cancer drug. non-collagenous 1 bovine pulmonary arterial endothelial cells a human umbilical vein endothelial cells fetal calf serum phosphate-buffered saline polyacrylamide gel electrophoresis Dulbecco's modified Eagle's medium bromodeoxyuridine basis fibroblast growth factor 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide tumor necrosis factor-α high performance liquid chromatography reduced and alkylated Tumor growth and metastasis are dependent on angiogenesis, the formation of new blood vessels from pre-existing ones (1Folkman J. Nat. Med. 1995; 1: 27-31Crossref PubMed Scopus (7188) Google Scholar, 2Folkman J. Ann. Surg. 1972; 175: 409-416Crossref PubMed Scopus (1063) Google Scholar). Growth factors and cytokines released from tumor cell components stimulate the endothelial cells of blood vessels leading to the expansion of tumor tissue (1Folkman J. Nat. Med. 1995; 1: 27-31Crossref PubMed Scopus (7188) Google Scholar). A theory of an “angiogenic switch” has been recently proposed, where the net balance of pro-angiogenic molecules and anti-angiogenic molecules are hypothesized to regulate the “on” and the “off,” respectively, of such a switch (1Folkman J. Nat. Med. 1995; 1: 27-31Crossref PubMed Scopus (7188) Google Scholar). Recent studies have identified several endogenous anti-angiogenic molecules producedde novo which regulate angiogenesis and tumor growth (3Jimenez B. Volpert O.V. Crawford S.E. Febbraio M. Silverstein R.L. Bouck N. Nat. Med. 2000; 6: 41-48Crossref PubMed Scopus (845) Google Scholar, 4O'Reilly M.S. Holmgren L. Shing Y. Chen C. Rosenthal R.A. Moses M. Lane W.S. Cao Y. Sage E.H. Folkman J. Cell. 1994; 79: 315-328Abstract Full Text PDF PubMed Scopus (3151) Google Scholar, 5O'Reilly M.S. Boehm T. Shing Y. Fukai N. Vasios G. Lane W.S. Flynn E. Birkhead J.R. Olsen B.R. Folkman J. Cell. 1997; 88: 277-285Abstract Full Text Full Text PDF PubMed Scopus (4221) Google Scholar, 6Kamphaus G.D. Colorado P.C. Panka D.J. Hopfer H. Ramchandran R. Torre A. Maeshima Y. Mier J.W. Sukhatme V.P. Kalluri R. J. Biol. Chem. 2000; 275: 1209-1215Abstract Full Text Full Text PDF PubMed Scopus (407) Google Scholar, 7Colorado P.C. Torre A. Kamphaus G. Maeshima Y. Hopfer H. Takahashi K. Volk R. Zamborsky E.D. Herman S. Ericksen M.B. Dhanabal M. Simons M. Post M. Kufe D.W. Weichselbaum R.R. Sukhatme V.P. Kalluri R. Cancer Res. 2000; 60: 2520-2526PubMed Google Scholar, 8Maeshima Y. Colorado P.C. Torre A. Holthaus K.A. Grunkemeyer J.A. Ericksen M.D. Hopfer H. Xiao Y. Stillman I.E. Kalluri R. J. Biol. Chem. 2000; 275: 21340-21348Abstract Full Text Full Text PDF PubMed Scopus (328) Google Scholar). Basement membranes are composed of thin layers of specialized extracellular matrix that provide the scaffold for epithelial and endothelial cells (9Paulsson M. Crit. Rev. Biochem. Mol. Biol. 1992; 27: 93-127Crossref PubMed Scopus (465) Google Scholar). Basement membranes also influence differentiation, proliferation, and migration of various cell types. Vascular basement membranes are located as insoluble structural walls in capillaries and they interact with endothelial cells. They are speculated to play an important role in regulating angiogenesis (7Colorado P.C. Torre A. Kamphaus G. Maeshima Y. Hopfer H. Takahashi K. Volk R. Zamborsky E.D. Herman S. Ericksen M.B. Dhanabal M. Simons M. Post M. Kufe D.W. Weichselbaum R.R. Sukhatme V.P. Kalluri R. Cancer Res. 2000; 60: 2520-2526PubMed Google Scholar, 10Madri J.A. Transpl. Immunol. 1997; 5: 179-183Crossref PubMed Scopus (59) Google Scholar,11Kalluri R. Sukhatme V.P. Curr. Opin. Nephrol. Hypertens. 2000; 9: 413-418Crossref PubMed Scopus (83) Google Scholar). Type IV collagen is one of the major macromolecular constituent of basement membranes (12Timpl R. Curr. Opin. Cell Biol. 1996; 8: 618-624Crossref PubMed Scopus (551) Google Scholar) and is expressed as six distinct α-chains, namely, α1-α6 (13Prockop D.J. Kivirikko K.I. Annu. Rev. Biochem. 1995; 64: 403-434Crossref PubMed Scopus (1368) Google Scholar). These α-chains are assembled into triple helices which further form a network to provide a scaffold for other macromolecules of the basement membrane. These α-chains are composed of three domains, the N-terminal 7 S domain, the middle triple helical domain, and the C-terminal globular non-collagenous domain (NC1)1 (14Timpl R. Wiedemann H. van Delden V. Furthmayr H. Kuhn K. Eur. J. Biochem. 1981; 120: 203-211Crossref PubMed Scopus (653) Google Scholar). Type IV collagen is thought to be important in endothelial cell proliferation and behavior during the angiogenic process (6Kamphaus G.D. Colorado P.C. Panka D.J. Hopfer H. Ramchandran R. Torre A. Maeshima Y. Mier J.W. Sukhatme V.P. Kalluri R. J. Biol. Chem. 2000; 275: 1209-1215Abstract Full Text Full Text PDF PubMed Scopus (407) Google Scholar, 7Colorado P.C. Torre A. Kamphaus G. Maeshima Y. Hopfer H. Takahashi K. Volk R. Zamborsky E.D. Herman S. Ericksen M.B. Dhanabal M. Simons M. Post M. Kufe D.W. Weichselbaum R.R. Sukhatme V.P. Kalluri R. Cancer Res. 2000; 60: 2520-2526PubMed Google Scholar, 10Madri J.A. Transpl. Immunol. 1997; 5: 179-183Crossref PubMed Scopus (59) Google Scholar). The NC1 domain of type IV collagen plays a crucial role in the assembly of type IV collagen to form trimers, and thus influences basement membrane organization, which is important for new blood vessel formation (10Madri J.A. Transpl. Immunol. 1997; 5: 179-183Crossref PubMed Scopus (59) Google Scholar,12Timpl R. Curr. Opin. Cell Biol. 1996; 8: 618-624Crossref PubMed Scopus (551) Google Scholar, 15Tsilibary E.C. Reger L.A. Vogel A.M. Koliakos G.G. Anderson S.S. Charonis A.S. Alegre J.N. Furcht L.T. J. Cell Biol. 1990; 111: 1583-1591Crossref PubMed Scopus (46) Google Scholar). Recently, we identified that α3(IV)NC1 (termed “tumstatin”) possessed a novel anti-angiogenic activity, and the activity was localized to amino acids 54–132 (tum-5) using deletion mutagenesis of tumstatin (8Maeshima Y. Colorado P.C. Torre A. Holthaus K.A. Grunkemeyer J.A. Ericksen M.D. Hopfer H. Xiao Y. Stillman I.E. Kalluri R. J. Biol. Chem. 2000; 275: 21340-21348Abstract Full Text Full Text PDF PubMed Scopus (328) Google Scholar, 16Petitclerc E. Boutaud A. Prestayko A. Xu J. Sado Y. Ninomiya Y. Sarras Jr., M.P. Hudson B.G. Brooks P.C. J. Biol. Chem. 2000; 275: 8051-8061Abstract Full Text Full Text PDF PubMed Scopus (274) Google Scholar). Integrin αvβ3 is involved in interactions between angiogenic vascular cells and extracellular matrix and it potentially plays a critical role in promoting angiogenesis and in endothelial cell survival (17Brooks P.C. Clark R.A. Cheresh D.A. Science. 1994; 264: 569-571Crossref PubMed Scopus (2721) Google Scholar, 18Brooks P.C. Montgomery A.M. Rosenfeld M. Reisfeld R.A. Hu T. Klier G. Cheresh D.A. Cell. 1994; 79: 1157-1164Abstract Full Text PDF PubMed Scopus (2170) Google Scholar). In this regard, we recently showed that tumstatin and the active tum-5 deletion mutant bind to αvβ3 integrin (19Maeshima Y. Colorado P.C. Kalluri R. J. Biol. Chem. 2000; 275: 23745-23750Abstract Full Text Full Text PDF PubMed Scopus (232) Google Scholar, 20Maeshima Y. Manfredi M. Reimer C. Holthaus K.A. Hopfer H. Chandamuri B.R. Kharbanda S. Kalluri R. J. Biol. Chem. 2001; 276: 15240-15248Abstract Full Text Full Text PDF PubMed Scopus (206) Google Scholar). The anti-angiogenic activity of tumstatin or tum-5 is not dependent on disulfide bond formation (20Maeshima Y. Manfredi M. Reimer C. Holthaus K.A. Hopfer H. Chandamuri B.R. Kharbanda S. Kalluri R. J. Biol. Chem. 2001; 276: 15240-15248Abstract Full Text Full Text PDF PubMed Scopus (206) Google Scholar). This prompted us to examine further the anti-angiogenic site within tum-5 using a synthetic peptide strategy. We synthesized eight, overlapping peptides covering the tum-5 domain, and tested these peptides in several anti-angiogenic assays. We demonstrate that the anti-angiogenic property is localized to a 25-amino acid region of tumstatin. This activity was not dependent on the disulfide bond linkage between cysteine residues. These results provide a novel peptide fragment as a possible drug candidate in the treatment of diseases dependent on angiogenesis. Recombinant tumstatin was expressed using 293 human embryonic kidney cells as previously described (8Maeshima Y. Colorado P.C. Torre A. Holthaus K.A. Grunkemeyer J.A. Ericksen M.D. Hopfer H. Xiao Y. Stillman I.E. Kalluri R. J. Biol. Chem. 2000; 275: 21340-21348Abstract Full Text Full Text PDF PubMed Scopus (328) Google Scholar). Deletion mutants of tumstatin (tum-1–5) with a 6-histidine tag were expressed in Escherichia coli as previously described (8Maeshima Y. Colorado P.C. Torre A. Holthaus K.A. Grunkemeyer J.A. Ericksen M.D. Hopfer H. Xiao Y. Stillman I.E. Kalluri R. J. Biol. Chem. 2000; 275: 21340-21348Abstract Full Text Full Text PDF PubMed Scopus (328) Google Scholar). Briefly, the sequence encoding the deletion mutants (tum-1–5) of tumstatin was amplified using polymerase chain reaction from the α3(IV)NCI/pDS vector (8Maeshima Y. Colorado P.C. Torre A. Holthaus K.A. Grunkemeyer J.A. Ericksen M.D. Hopfer H. Xiao Y. Stillman I.E. Kalluri R. J. Biol. Chem. 2000; 275: 21340-21348Abstract Full Text Full Text PDF PubMed Scopus (328) Google Scholar, 21Neilson E.G. Kalluri R. Sun M.J. Gunwar S. Danoff T. Mariyama M. Myers J.C. Reeders S.T. Hudson B.G. J. Biol. Chem. 1993; 268: 8402-8405Abstract Full Text PDF PubMed Google Scholar). The resulting cDNA fragment was ligated into pET28a(+) (Novagen, Madison, WI). Each recombinant protein was expressed in E. coli and purified using Ni-NTA-agarose column (Qiagen). The amino acids 45–132 of tumstatin were expressed as tum-5 which includes the N-terminal 9 amino acids in addition to the previously identified anti-angiogenic domain (54–132 amino acids) (8Maeshima Y. Colorado P.C. Torre A. Holthaus K.A. Grunkemeyer J.A. Ericksen M.D. Hopfer H. Xiao Y. Stillman I.E. Kalluri R. J. Biol. Chem. 2000; 275: 21340-21348Abstract Full Text Full Text PDF PubMed Scopus (328) Google Scholar). The additional 9 amino acids were added to enhance the efficiency of protein expression. Only soluble protein with a low endotoxin level (less than 50 enzyme units/mg) was used in the present study. Synthetic peptides CDCRGDCFC (RGD-4C) and control peptides CNGRC were kindly provided by Ilex Oncology, Inc. (San Antonio, TX). T1 peptide consisting of the N-terminal 20 amino acids of tumstatin, and T2-T7 peptides covering 54–132 amino acids of tumstatin were also kindly provided by Ilex Oncology, Inc. (Table I). T8 peptide (69–95 amino acid) was synthesized with mutation of Leu to Lys at position 69. These peptides were synthesized and characterized as previously described (22Arap W. Pasqualini R. Ruoslahti E. Science. 1998; 279: 377-380Crossref PubMed Scopus (1852) Google Scholar).Table ISequence of peptides derived from tumstatin (amino acid)150, T8 peptide: Leu at position 69 mutated to Lys. 150, T8 peptide: Leu at position 69 mutated to Lys. In some experiments, tumstatin and tum-5 were processed for reduction and alkylation as described elsewhere (23Crestfield A.M. Moore S. Stein W.H. J. Biol. Chem. 1963; 238: 622-627Abstract Full Text PDF PubMed Google Scholar, 24Kalluri R. Gunwar S. Reeders S.T. Morrison K.C. Mariyama M. Ebner K.E. Noelken M.E. Hudson B.G. J. Biol. Chem. 1991; 266: 24018-24024Abstract Full Text PDF PubMed Google Scholar). Briefly, 2.5 mg/ml tum-5 or tumstatin in 6 m guanidine-HCl, 20 mm Tris-HCl (pH 7.5) were incubated for 1 h at 50 °C in 10 mmdithiothreitol. The reaction mixture was then brought to room temperature, and iodoacetamide was added to make the final concentration 25 mm. Following incubation for 1 h at room temperature, the resulting solution was dialyzed against 5 mm HCl (two changes, 5 h each) and finally against 1 mm HCl. The absence of free thiol groups in the final product was confirmed by using Ellman reagent. Tum-5, the recombinant deletion mutant of tumstatin, was analyzed by SDS-PAGE and Coomassie Blue staining as previously described (8Maeshima Y. Colorado P.C. Torre A. Holthaus K.A. Grunkemeyer J.A. Ericksen M.D. Hopfer H. Xiao Y. Stillman I.E. Kalluri R. J. Biol. Chem. 2000; 275: 21340-21348Abstract Full Text Full Text PDF PubMed Scopus (328) Google Scholar, 25Kalluri R. Sun M.J. Hudson B.G. Neilson E.G. J. Biol. Chem. 1996; 271: 9062-9068Abstract Full Text Full Text PDF PubMed Scopus (75) Google Scholar). Bovine pulmonary arterial endothelial cells (C-PAE), human umbilical vein endothelial cells (HUVEC), and the human prostate adenocarcinoma cell line (PC-3) were all obtained from American Type Culture Collection. These cell lines were maintained in DMEM (C-PAE; Life Technologies, Inc.) supplemented with 10% fetal calf serum (FCS), 100 units/ml of penicillin, and 100 mg/ml streptomycin, in EGM-2 (HUVEC; Clonetics, San Diego, CA), or in F12K (Mediatech, Herndon, VA). The melanoma cell line WM-164 was obtained from Dr. Meenhard Herlyn at the Wistar Institute (Philadelphia, PA), and maintained as previously described (19Maeshima Y. Colorado P.C. Kalluri R. J. Biol. Chem. 2000; 275: 23745-23750Abstract Full Text Full Text PDF PubMed Scopus (232) Google Scholar,26Herlyn D. Iliopoulos D. Jensen P.J. Parmiter A. Baird J. Hotta H. Adachi K. Ross A.H. Jambrosic J. Koprowski H. Cancer Res. 1990; 50: 2296-2302PubMed Google Scholar). A suspension of C-PAE cells (7,000 cells/well, passage 2–6) in DMEM containing 0.5% FCS were added to 96-well plates pre-coated with fibronectin. After 24 h, media was replaced with DMEM containing 20% FCS and either recombinant protein or synthetic peptide. Then, after 48 h, methylene blue staining was performed as previously described (8Maeshima Y. Colorado P.C. Torre A. Holthaus K.A. Grunkemeyer J.A. Ericksen M.D. Hopfer H. Xiao Y. Stillman I.E. Kalluri R. J. Biol. Chem. 2000; 275: 21340-21348Abstract Full Text Full Text PDF PubMed Scopus (328) Google Scholar). All groups represent triplicate samples. WM-164 and PC-3 cells were analyzed using a similar protocol. In some assays, plates were coated with vitronectin (2.5 µg/ml) or a mixture of type I collagen (10 µg/ml), vitronectin (2.5 µg/ml), and fibronectin (10 µg/ml). In these assays, when treatment of cells were started, the same final concentration of vitronectin or the mixture of three-matrix components were further added. The BrdUrd incorporation assay was conducted using the BrdUrd proliferation assay kit according to the manufacturer's instructions (Calbiochem) with some modifications. Briefly, C-PAE cells were seeded onto 96-well plates in DMEM containing 10% FCS. The next day the medium was replaced with DMEM containing 2% FCS with or without tum-5 or full-length tumstatin (293 cell expressed). The plates were then incubated for 46 h at which time cells were pulsed for 2 h with BrdUrd (10 nm). The cells/DNA were then fixed to the wells, reacted with anti-BrdUrd primary and secondary antibodies, and then developed using a colorimetric reaction. The plates were read atA 450 nm on a Molecular Devices plate reader. All groups represent triplicate samples. C-PAE cells were plated onto 96-well plates and serum-depleted as described above. T3 peptide (20 µg/ml, final concentration) was incubated with varying concentrations of human αvβ3 integrin protein (Chemicon) for 30 min at room temperature. This mixture was then added onto the cells and incubated for 48 h at 37 °C. Proliferation assays were performed using the methylene blue staining method as previously described (8Maeshima Y. Colorado P.C. Torre A. Holthaus K.A. Grunkemeyer J.A. Ericksen M.D. Hopfer H. Xiao Y. Stillman I.E. Kalluri R. J. Biol. Chem. 2000; 275: 21340-21348Abstract Full Text Full Text PDF PubMed Scopus (328) Google Scholar). C-PAE cells were growth arrested by contact inhibition for 48 h. The 0 h value is the percentage of cells in S phase at this time point. The cells (0.2 × 106/well) were harvested and plated onto a fibronectin-coated, 6-well plate in 1% FCS supplemented with 3 ng/ml bFGF and tumstatin-derived synthetic peptides. After 24 h, cells were harvested and processed for staining with propidium iodide (5 µg/ml) as previously described (27Dhanabal M. Volk R. Ramchandran R. Simons M. Sukhatme V.P. Biochem. Biophys. Res. Commun. 1999; 258: 345-352Crossref PubMed Scopus (197) Google Scholar). The cells were analyzed using a Becton Dickinson FACStar plus flow cytometer. The Modfit software was used to calculate the percentage of cells in different phases of the cell cycle. Annexin V, a calcium-dependent phospholipid-binding protein with a high affinity for phosphatidylserine was used to detect apoptosis (28van Engeland M. Nieland L.J. Ramaekers F.C. Schutte B. Reutelingsperger C.P. Cytometry. 1998; 31: 1-9Crossref PubMed Scopus (1531) Google Scholar). Briefly, endothelial cells (0.5 × 106/well) were seeded onto a 6-well plate in 10% FCS containing DMEM. The next day, fresh medium containing 10% FCS was added together with either synthetic peptide or 80 ng/ml TNF-α. After 18 h of treatment, floating and attached cells were harvested and processed as described elsewhere (6Kamphaus G.D. Colorado P.C. Panka D.J. Hopfer H. Ramchandran R. Torre A. Maeshima Y. Mier J.W. Sukhatme V.P. Kalluri R. J. Biol. Chem. 2000; 275: 1209-1215Abstract Full Text Full Text PDF PubMed Scopus (407) Google Scholar). PC-3 cells were treated and processed as described above. Cell viability was assessed by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrasolium bromide, Chemicon) assay. C-PAE cells (7,000 cells/well) were plated in a 96-well plate in DMEM containing 10% FCS. The next day, 20 µg/ml synthetic peptide was added, cells were incubated for 24 h, and cell viability was evaluated as previously described (8Maeshima Y. Colorado P.C. Torre A. Holthaus K.A. Grunkemeyer J.A. Ericksen M.D. Hopfer H. Xiao Y. Stillman I.E. Kalluri R. J. Biol. Chem. 2000; 275: 21340-21348Abstract Full Text Full Text PDF PubMed Scopus (328) Google Scholar). TNF-α (80 ng/ml) was used as a positive control. Caspase-3 activity was determined as previously described (8Maeshima Y. Colorado P.C. Torre A. Holthaus K.A. Grunkemeyer J.A. Ericksen M.D. Hopfer H. Xiao Y. Stillman I.E. Kalluri R. J. Biol. Chem. 2000; 275: 21340-21348Abstract Full Text Full Text PDF PubMed Scopus (328) Google Scholar). Briefly, C-PAE cells (0.4 × 106/well) were plated in 6-cm Petri dishes precoated with fibronectin (10 µg/ml). Cells were serum-starved (2% FCS) for 24 h, and then stimulated with bFGF (3 ng/ml) in DMEM (2% FCS) containing T3 peptide (10 or 50 µg/ml). Controls received PBS buffer. TNF-α (80 ng/ml) was used as a positive control. After 24 h, both the supernatant and attached cells were combined and an equal number of cells (4 × 107 cells/ml) were processed following the manufacturers instruction (CLONTECH). A specific inhibitor of caspase-3, DEVD-fmk, was used for specificity. The absorbance was measured in a microplate reader (Bio-Rad) at 405 nm. Similarly, nonendothelial cells (PC-3) were used and analyzed. This assay was repeated three times. This assay was performed as previously described (19Maeshima Y. Colorado P.C. Kalluri R. J. Biol. Chem. 2000; 275: 23745-23750Abstract Full Text Full Text PDF PubMed Scopus (232) Google Scholar, 29Senger D.R. Claffey K.P. Benes J.E. Perruzzi C.A. Sergiou A.P. Detmar M. Proc. Natl. Acad. Sci. U. S. A. 1997; 94: 13612-13617Crossref PubMed Scopus (455) Google Scholar). 96-well plates were coated with 10 µg/ml recombinant protein or synthetic peptide overnight. Vitronectin (Collaborative Biomedical Products) was used at a concentration of 0.5–2.5 µg/ml for coating plates. Plates were blocked with 100 mg/ml bovine serum albumin (Sigma) for 2 h. HUVECs or C-PAEs (1.5 × 105 cells/ml, in M-199) were incubated with either 10 µg/ml antibody or synthetic peptide for 15 min. Then, 100 µl of the cell suspension was added to each well and incubated for 45 min at 37 °C. After washing, the number of attached cells was determined with methylene blue staining. Control mouse IgG1 and mouse monoclonal antibody to human β1 integrin (clone P4C10) were purchased from Life Technologies. Monoclonal antibody to human αv (clone NKI-M9), β3 (clone B3A), αvβ3 (clone LM609), and αvβ5 integrin (clone P1F6) were purchased from Chemicon. T3 peptide was dissolved in 10 ml of 50% acetonitrile, 10 mmammonium bicarbonate buffer (pH 7.3) at 0.25 mg/ml. Aliquots (30 µl) of 2 mg/ml potassium ferricyanide dissolved in 10 mmammonium bicarbonate buffer (pH 7.3) were added 5 times at room temperature to the peptide solution at 5-min intervals. The reaction mixture was shortly vortexed every time after the oxidizer was added, was allowed to stay for 2 h at room temperature. Then, the absence of free thiol groups in the peptide solution was confirmed using Ellman reagent. The absence of the peptide dimers and higher oligomers in a final reaction mixture was confirmed by SDS-PAGE (16.5%) and silver staining. HPLC was used for the final purification of the T3 peptide. T3 peptide was applied and run onto a C-18 300-Å Jupiter column (Phenomenex, CA) using an acetonitrile (CH3CN) gradient (20–60% buffer B, 30 min). Buffer A, 0.1% trifluoroacetic acid or buffer B, 0.1% trifluoroacetic acid in acetonitrile. An in vivo Matrigel plug assay was performed as previously described (8Maeshima Y. Colorado P.C. Torre A. Holthaus K.A. Grunkemeyer J.A. Ericksen M.D. Hopfer H. Xiao Y. Stillman I.E. Kalluri R. J. Biol. Chem. 2000; 275: 21340-21348Abstract Full Text Full Text PDF PubMed Scopus (328) Google Scholar). Five to six-week old male C57/BL6 mice (Jackson Laboratories, Bar Harbor, ME) were obtained. All animal studies were reviewed and approved by the animal care and use committee of Beth Israel Deaconess Medical Center and are in accordance with the guidelines of the Department of Health and Human Services. Matrigel (Collaborative Biomolecules) was mixed with 20 units/ml heparin (Pierce), 50 ng/ml vascular endothelial growth factor (R&D), and 10 µg/ml tum-1 or 10 µg/ml synthetic peptide. The control group received neither the proteins nor the peptides. The Matrigel mixture was injected subcutaneously, and after 6 days mice were sacrificed and the Matrigel plugs were removed and fixed in 4% paraformaldehyde. The plugs were embedded in paraffin, sectioned, and H & E stained. Sections were examined by light microscopy, and the number of blood vessels from 4 to 7 high power fields (×400) was counted and averaged. All sections were coded and observed by an investigator who was blinded for study protocols. Each group consists of three or four Matrigel plugs. Female nude NCRNU mice, 5–6 weeks old, weighing ∼20 g were implanted with 2 × 106MDAMB-435 cells into the subaxillary mammary fat pad. The tumors were measured using Vernier calipers and the volume was calculated using the standard formula (width2 × length × 0.52) (4O'Reilly M.S. Holmgren L. Shing Y. Chen C. Rosenthal R.A. Moses M. Lane W.S. Cao Y. Sage E.H. Folkman J. Cell. 1994; 79: 315-328Abstract Full Text PDF PubMed Scopus (3151) Google Scholar, 5O'Reilly M.S. Boehm T. Shing Y. Fukai N. Vasios G. Lane W.S. Flynn E. Birkhead J.R. Olsen B.R. Folkman J. Cell. 1997; 88: 277-285Abstract Full Text Full Text PDF PubMed Scopus (4221) Google Scholar). When the tumors were 100 mm3, the animals were pair-matched into treatment and control groups (7 mice per group). Initial doses of tum-5 or vehicle control were given on the day of pair-matching (day 1), and were administered via intraperitoneal injection bi-daily at the doses indicated. Mice were weighed twice weekly, and tumor measurements were taken by calipers twice weekly, starting on day 1. Mean fractional tumor volume ratios (V/V o) were plotted against time. Mice were euthenized at the end of the treatment period. Upon termination, the mice were weighed, sacrificed, and their tumors were excised. The mean tumor weight per group was calculated, and the mean treated tumor ratio/mean control tumor ratio × 100 was subtracted from 100% to give the tumor growth inhibition for each group. All values are expressed as mean ± S.E. ANOVA with a one tailed Student's t test was used to identify significant differences in multiple comparisons. A level ofp < 0.05 was considered statistically significant. Recombinant tumstatin was reduced and alkylated (RA) to remove the disulfide bond linkages (Fig. 1, panel A). As expected, by SDS-PAGE the RA tumstatin migrated slower than non-reduced tumstatin. Similarly, deletion mutant tum-5 was also reduced and alkylated. Non-reduced tum-5 can exist as a monomer, dimer, and other multimers (Fig. 1, panel B). RA tum-5 migrates as a single band corresponding to a monomeric protein with molecular mass of ∼12 kDa, with retarded mobility compared with unreduced tum-5 monomer (Fig. 1, panel B). RA tumstatin and RA tum-5 were used in an endothelial cell proliferation assay and compared with the non-reduced protein. Reduction and alkylation of tumstatin and tum-5, did not influence their anti-endothelial cell proliferative activity (Fig. 1,panels C and D). We examined the effect of soluble human tum-5 and RA tum-5 on established primary human orthotopic breast tumors in nude mice. No evident toxicity was observed in any groups, as judged by weight change and terminal autopsy. Both human tum-5 and human tum-5/RA significantly inhibited the growth of MDA MB435 human breast carcinoma xenografts (Fig. 1, panel E). Human tum-5 at 1 mg/kg had a tumor growth inhibition of 37.1% (p = 0.03) and human tum-5/RA at 0.2 and 5 mg/kg had a tumor growth inhibition of 45.6% (p = 0.001) and 45.3% (p = 0.002), respectively, as compared with the vehicle injected control group. These experiments suggest that reduction and alkylation of tum-5 does not alter the in vivo effects of tum-5 in inhibition of tumor growth. These results strongly suggest tum-5 activity is independent of disulfide bond linkage. Our results show that disulfide linkage is not critical for the anti-angiogenic activity of tumstatin. This very interesting structural feature of tumstatin and its active deletion mutant tum-5, allowed us to pursue a synthetic peptide strategy to identify the amino acid sequence responsible for the anti-angiogenic function of tumstatin. Since the entire anti-angiogenic activity of tumstatin is contained within deletion mutant tum-5 (20Maeshima Y. Manfredi M. Reimer C. Holthaus K.A. Hopfer H. Chandamuri B.R. Kharbanda S. Kalluri R. J. Biol. Chem. 2001; 276: 15240-15248Abstract Full Text Full Text PDF PubMed Scopus (206) Google Scholar), our initial strategy was to synthesize 5 overlapping 2